Sleep Apnea in Orthodontics – A review - P, Kalyani; Kumar, Naveen; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To review the effect of sleep apnea and its management in orthodontics. Background: Sleep apnea is a serious sleep disorder that occurs when a person’s breathing is interrupted during sleep. There are two types of sleep apnea, obstructive sleep apnea and central sleep apnea. Obstructive sleep apnea syndrome is a common, chronic disorder of sleep and breathing that causes disability from pathologic sleepiness and respiratory and cardiovascular complications. OSA is re- lated to upper airway obstruction that develops during sleep with manifestations that include snoring, apneas and hypopneas. Several oral devices have been designed to treat sleep apnea. One of the most common devices used are the orthodontic appliances. Reason: The review elaborates on the different types of orthodontic appliances used in the treatment of sleep apnea and also their effectiveness.